Study of Waste, Air Emissions, and Sustainability Initiatives in West-Australian Small-Medium Manufacturing Industries - Latunij, Ferdinand; John, Michele; Mullins, Benjamin (Berlin Institute of Technology, Berlin, Germany, Middle East Technical Uni, Ankara, Turkey, 2012)
Small and medium-sized Industries represent approximately 40% of Australian industry [1], however are estimated to be responsible for 70% of industrial pollution [2,3,4]. Despite this, environmental regulations to which large companies must comply with are often not applicable to SMEs. This study examines wastes and air emissions generated by SMEs in the Western Australian manufacturing sector. The study consisted of (1) face-to-face surveys of 42 SMEs in Perth, Western Australia; (2) detailed waste and energy audits for a sub-group of the above; and (3) exploring innovative sustainability approaches for SMEs to reduce wastes and air emissions. A relatively small number of initiatives to reduce wastes and emissions undertaken by the SMEs were found such as investing in improved technologies or equipment, and utilising waste streams as inputs for other business operations. A decrease in the uptake of sustainability initiatives was evident compared to previous studies in the region. The paper presents an overview of the findings of the study, as well as the barriers to the uptake of sustainability initiatives among the SMEs for reducing their wastes and air emissions.